2013
DOI: 10.1155/2013/364802
|View full text |Cite
|
Sign up to set email alerts
|

Function ofTiO2Lattice Defects toward Photocatalytic Processes: View of Electronic Driven Force

Abstract: Oxygen vacancies and Ti-related defects (OTDs) are the main lattice defects ofTiO2, which have great influence on its photocatalytic activity. To understand the relationship between the defects and photocatalytic activities, detailed discussions based on the electronic driven force provided by these defects are carried out during the three commonly accepted processes in photocatalytic reactions. It is found that these defects inevitably (i) influence the energy structure of the pristineTiO2as the isolate accep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 123 publications
0
5
0
Order By: Relevance
“…[256] As already mentioned, that V O" primarily acts as acceptor species, after accepting an electron, the formation of V O makes it to behave more like a donor than acceptor site during photocatalytic reaction. [257] The extra electron in V O situated in sub-surface could also recombine with a hole to further reduce Ti 4+ to Ti 3+ , hence preventing electrons to approach Ti at that site. The process continues to transfer the aligned Ti 4+ to regenerate the initial V O state throughout the photocatalytic process.…”
Section: Carrier Trapping and Distribution Of Chargesmentioning
confidence: 99%
See 1 more Smart Citation
“…[256] As already mentioned, that V O" primarily acts as acceptor species, after accepting an electron, the formation of V O makes it to behave more like a donor than acceptor site during photocatalytic reaction. [257] The extra electron in V O situated in sub-surface could also recombine with a hole to further reduce Ti 4+ to Ti 3+ , hence preventing electrons to approach Ti at that site. The process continues to transfer the aligned Ti 4+ to regenerate the initial V O state throughout the photocatalytic process.…”
Section: Carrier Trapping and Distribution Of Chargesmentioning
confidence: 99%
“…The process continues to transfer the aligned Ti 4+ to regenerate the initial V O state throughout the photocatalytic process. [257] However, this kind of migration increases the rate of recombination processes with longer travel pathways. Likewise, the electrons can be transferred to the nearby dissociative adsorbed species by the surface V O if the electrons are approaching along the surface Tiatoms.…”
Section: Carrier Trapping and Distribution Of Chargesmentioning
confidence: 99%
“…[21][22][23][24][25][26]. Some results demonstrated that surface defects may serve as electron traps, making the electrons migrate to a more reactive site, or directly out of the surface [27][28][29][30]. Subsequently, reactions will occur between the surface adsorbed reactants and the escaped electrons.…”
Section: Introductionmentioning
confidence: 99%
“…Structural or point defects at the particle surface can act as photoactive centers through capture of photogenerated charge carriers, and as adsorption centers of reagents leading ultimately to intermediates and end reaction products. Consequently, structural defects in VLA solids are fundamental in complex multiple‐phase cycles of photoassisted reactions ,. Moreover, existing defects in solids cause light to be absorbed within the extrinsic spectral region at photon energies lower than the intrinsic absorption limit (i. e., at E hν < E bg ).…”
Section: Introductionmentioning
confidence: 99%